PENERAPAN PENDEKATAN KONSTRUKTIVIS UNTUK MENINGKATKAN AKTIVITAS DAN PEMAHAMAN KONSEP BILANGAN BULAT PADA SISWA KELAS VIIB MTS. JIHADUL UMMAH TAHUN PEMBELAJARAN 2024/2025 - Yunus, Muhamad (Noble Cendekia Indonesia, 2024)
The learning process is still dominated by lectures and teacher-centered activities. Students' activities only involve listening to the teacher's explanations and noting down what they consider important, which affects their learning outcomes. The method that has been used so far does not adequately help students engage actively both intellectually and emotionally in learning, especially in mathematics. The problem in this research is how the constructivist approach is applied to MTs Jihadul Ummah students so that it can improve the understanding of integer concepts. The goal to be achieved in this research is to improve students' understanding of the material provided and the completeness of learning outcomes. This research was conducted using a quantitative approach to process learning outcome data and a qualitative approach to process observational data. This research was conducted on the students of class VIIB MTs. Jihadul Ummah for the 2024/2025 academic year. The results of the evaluation and observation are to see the abilities and activities of the students during the learning process, and the data are analyzed using the completeness of learning. A learning completeness of 75% is an indicator used to determine the improvement in academic achievement. The research results show an increase in the average student learning outcomes, with an initial stage score of 67.00 and a completion percentage of 65.62%. Meanwhile, at the final stage, the average student learning outcome score was 69.8 with a completeness rate of 81.25%. With the implementation of the constructivist model, the learning of the topic of integers can enhance the understanding of mathematical concepts and apparently can make students enthusiastic and motivated in learning mathematics, thereby actively engaging them both intellectually and emotionally